Reduction of hypervalent chromium in acidic media by alginic acid - Bertoni, Fernando Ariel (2014)
Selective oxidation of carboxylate groups present in alginic acid by CrVI affords CO2, oxidized alginic acid, and CrIII as final products. The redox reaction afforded first-order kinetics in [alginic acid], [CrVI], and [H+], at fixed ionic strength and temperature. Kinetic studies showed that the redox reaction proceeds through a mechanism which combines CrVI →CrIV → CrII and CrVI → CrIV → CrIII pathways. The mechanism was supported by the observation of free radicals, CrO22+ and CrV as reaction intermediates. The reduction of CrIV and CrV by alginic acid was independently studied and it was found to occur more than 103 times faster than alginic acid/CrVI reaction, in acid media. At pH 1–3, oxo-chromate(V)–alginic acid species remain in solution during several hours at 15 °C. The results showed that this abundant structural polysaccharide present on brown seaweeds is able to reduce CrVI/V/IV or stabilize high-valent chromium depending on pH value.